Intrusive reawakening of El Chichón volcano prior to its Holocene eruptive hyperactivity - Cisneros de León, Alejandro; Schmitt, Axel Karl (Journal of volcanology and geothermal research, 2019)
El Chichón volcano in southeastern Mexico (Chiapas) has produced compositionally homogeneous trachyandesite throughout its ca. 372kyr eruptive history, but crystal-scale heterogeneity reveals a complex interplay between magmas generated and stored at different crustal levels. High-sensitivity ion microprobe 238U-230Th zircon dating from the last two eruptions of El Chichón (1982 and 550 BP) demonstrates that most zircon crystallized between 0 and ca. 40ka. Few zircon crystals date back to ca. 130kyr, and none to the Middle Pleistocene phase of eruptions. Trace elements and oxygen isotope variations in zircon indicate fairly stable conditions in the magma chamber between ca. 20 and 130ka, with average Ti-in-zircon temperatures estimated at 712°C and δ18O values of +6.6‰. However, excursions to high Ti-in-zircon temperatures and high δ18O values in zircon occurred at ca. 24ka. These excursions also mark the onset of subsequent progressive changes to occasionally higher Ti-in-zircon temperatures, lower δ18O values, and more primitive magma compositions (e.g., high Eu/Eu*, Zr/Hf and Th/U). Systematic rim-ward decrease in δ18O is recorded by juvenile zircon domains which quasi-continuously crystallized for up to 30kyr prior to eruption. Textural relationships and O-isotopic variations within single zircon crystals are thus evidence for magma recharge causing initial resorption of xenocrystic zircon, rapid zircon re-saturation driven by local supersaturation, and effective magma mixing with sediment-contaminated high-δ18O melts from a boundary layer at the contact of the magma reservoir to country rock. Initial thermal and compositional defrosting of an intermediate boundary layer and its crystal cargo may have been rapid due to the brief duration of high-temperature recharge events, as evidenced by the preservation of zircon xenocrysts. The delay of at least 12kyr between major recharge episodes recorded by zircon and the onset of Holocene eruptions at brief recurrence intervals suggests that frequent eruptions only started when trachybasaltic magma recharge continued or intensified during the Holocene.
Gesehen am 21.08.2019